Book Review: AN EXCEPTIONAL EDITORIAL RELEASE: “A TRIBUTE TO GYÖRGY LIGETI IN HIS NATIVE TRANSYLVANIA” - LUPU, Olguța (Studia Universitatis Babes-Bolyai Musica, 2020)
The volume A Tribute to György Ligeti in His Native Transylvania (nos. 1-2) is quite an event in Romanian musicology. Edited by distinguished musicologists Bianca Țiplea Temeș and Kofi Agawu, the volume enjoys the contribution of fifteen researchers from various cultures, schools, and generations – in keeping with multicultural Transylvania, Ligeti’s place of origin. The idea to pay him homage in Cluj-Napoca, the very city the composer studied in between 1941-43, was Bianca Țiplea Temeș’, the musicologist and professor at the “Gheorghe Dima” National Academy of Music, founder and director of the festival “A Tribute to György Ligeti in His Native Transylvania” whose first edition in 2006 marked the composer’s 10th death anniversary. The volume joins papers presented on the conferences hosted by the festival in 2016 and 2018, and the binary structuration, with each part bearing the title of the corresponding conference, offers a clear image of the two events.